Temperature changes, household consumption, and internal migration: Evidence from Tanzania - Hirvonen, Kalle (Wiley, 2016)
Large rural‐urban wage gaps observed in many developing countries are suggestive of barriers to migration that keep potential migrants in rural areas. Using long panel data spanning nearly two decades, I study the extent to which migration rates are constrained by liquidity constraints in rural Tanzania. The analysis begins by quantifying the impact of weather variation on household welfare. The results show how household consumption co‐moves with temperature, rendering households vulnerable to local weather events. These temperature‐induced income shocks are then found to inhibit long‐term migration among men, thus preventing them from tapping into the opportunities brought about by geographical mobility.